A role for TGFβ signalling in medium spiny neuron differentiation of human pluripotent stem cells. Issue 2 (6th May 2020) - Fjodorova, Marija; Noakes, Zoe; Li, Meng
Abstract: Activin A and other TGFβ family members have been shown to exhibit a certain degree of promiscuity between their family of receptors. We previously developed an efficient differentiation protocol using Activin A to obtain medium spiny neurons (MSNs) from human pluripotent stem cells (hPSCs). However, the mechanism underlying Activin A-induced MSN fate specification remains largely unknown. Here we begin to tease apart the different components of TGFβ pathways involved in MSN differentiation and demonstrate that Activin A acts exclusively via ALK4/5 receptors to induce MSN progenitor fate during differentiation. Moreover, we show that Alantolactone, an indirect activator of SMAD2/3 signalling, offers an alternative approach to differentiate hPSC-derived forebrain progenitors into MSNs. Further fine tuning of TGFβ pathway by inhibiting BMP signalling with LDN193189 achieves accelerated MSN fate specification. The present study therefore establishes an essential role for TGFβ signalling in human MSN differentiation and provides a fully defined and highly adaptable small molecule-based protocol to obtain MSNs from hPSCs.